2018
DOI: 10.13036/17533562.59.4.003
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural properties of d0 ion-doped silicate glasses for photovoltaic applications

Abstract: Optical and structural properties of float-type soda lime silicate (SLS) glasses doped with 0.2 mol % TiO 2 , ZrO 2 , HfO 2 , Nb 2 O 5 , Ta 2 O 5 , MoO 3 or WO 3 have been studied. Under UV excitation all d 0 doped glasses exhibit broadband visible emission centred between 19,000 cm-1 and 25,000 cm-1 (400nm-525nm) due to a transition from the 2p orbital of O 2to the metal d 0 orbital. Dopant additions lead to shifts in the UV absorption edge to lower energies, with doped glasses having an absorption edge 2,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 68 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…Ion incorporation of Cu + by exchange has also shown promise 52 . In addition, recent research by some of the present authors 63,64 has demonstrated that a number of second‐ and third‐row transition metal dopants which adopt the d 0 electronic configuration in glasses (Ti 4+ , Zr 4+ , Hf 4+ , Nb 5+ , Ta 5+ , Mo 6+ and W 6+ ), 63 and also heavy metal cations such as Sb which exhibit far‐UV absorption bands from s → p electronic transitions 65 can also provide down‐shifting of UV photons in silicate glasses with negligible visible absorption 63 . Moreover, some of the present authors have also shown that adding Gd 3+ or other lanthanides as a co‐dopant with Bi 3+ can provide enhanced luminescence intensity compared with Bi 3+ doping alone 64…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Ion incorporation of Cu + by exchange has also shown promise 52 . In addition, recent research by some of the present authors 63,64 has demonstrated that a number of second‐ and third‐row transition metal dopants which adopt the d 0 electronic configuration in glasses (Ti 4+ , Zr 4+ , Hf 4+ , Nb 5+ , Ta 5+ , Mo 6+ and W 6+ ), 63 and also heavy metal cations such as Sb which exhibit far‐UV absorption bands from s → p electronic transitions 65 can also provide down‐shifting of UV photons in silicate glasses with negligible visible absorption 63 . Moreover, some of the present authors have also shown that adding Gd 3+ or other lanthanides as a co‐dopant with Bi 3+ can provide enhanced luminescence intensity compared with Bi 3+ doping alone 64…”
Section: Introductionmentioning
confidence: 56%
“…In these calls, one of the key topics has been ‘Solar glasses and encapsulation materials’. The LIMES project addressed several aspects that are relevant for PV cover glasses and investigated optical, 63 mechanical and chemical properties of glass as well as novel thermal toughening methods 97 and also the addition of antireflective and self‐cleaning capabilities to the glass surface 98,99 . The glasses made in laboratory experiments were used for proof‐of‐concept studies by making the 70 × 70 mm PV modules discussed here.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of cover glass for PV modules, the trend has been to use low-iron glass to increase transmitted light (Deubener et al, 2009). A drawback to this type of glass is that a larger amount of high-energy UV radiation is transmitted, which is harmful to the encapsulation material EVA that is used in most PV modules today (Allsopp et al, 2018). When UV radiation below 350 nm reaches the PV module, both the semiconductor material (Osterwald et al, 2003) and the laminate (Kuitche et al, 2014;Oliveira et al, 2018) are degraded.…”
Section: Introductionmentioning
confidence: 99%
“…With the increased optical, chemical and mechanical properties of the glasses developed, the use of thinner glass front sheets is enabled, reducing the weight and cost of PV modules. This has been exploited through a patent application [1] and a publication [2]. 28 Two main bodies of work were completed focussing on d 0 cations comprising transition metal oxides of titanium, zirconium, hafnium, niobium, tantalum, molybdenum and tungsten outlined in Chapter 4.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Separation of these charge carriers before they are able to recombine 4. Transportation of the charge carriers through electrical contacts and movement through a circuit to generate work A photon of energy equal to or slightly higher than the bandgap of the semiconductor is absorbed (1), exciting an electron to the conduction band (2). Due to the nature of semiconductor junctions, the electron can only move towards the negative terminal and the hole moves in the opposite direction (3).…”
Section: Photovoltaic Effectmentioning
confidence: 99%